Bank capital - Orgler, Yair E.; Wolkowitz, Benjamin (New York : Van Nostrand Reinhold Co., 1976)
The subject of bank capital has been attracting attention for a long time. Bank capital is now widely considered one of the most important issues in banking.
Includes bibliographies and index.
osc 02/06/17
Loans
Keywords: Banks and Banking; United States